Knowledge and skills transfer amongst diagnostic radiographers and students: experiences from the public healthcare professionals in the Free State - Wasserman, Jason Clint (Central University of Technology, 2025)
In the context of diagnostic radiography in South Africa, the effective transfer of knowledge and skills between diagnostic radiographers and students is crucial for professional development and patient care. However, understanding the factors influencing this transfer is limited within the profession. The primary aim of this study was to investigate the factors affecting knowledge and skills transfer between diagnostic radiographers and students. The objectives were to describe and explore these factors in depth, differentiate between barriers and enablers, propose potential solutions, and develop an infographic as a tool for raising awareness and promoting effective knowledge and skills transfer in the clinical environment. A qualitative, exploratory-descriptive and contextual research design was used. Semi-structured interviews were conducted with 15 participants, including qualified radiographers, student radiographers and community service radiographers. The qualitative data obtained were analysed using reflexive thematic analysis to identify key focus areas and themes. The identified key focus areas for knowledge and skills transfer were enablers, barriers and possible solutions. The enablers included a safe and conducive working environment, personal attributes and preferred methods for learning. The study highlighted themes such as communication and supervision challenges, personal and interpersonal factors, workplace pressures and adaptation challenges as barriers. Participants emphasised professional development, and engagement and student placement strategies as possible solutions to overcome barriers obstructing knowledge and skills transfer. The themes and their respective codes underscored the complex interplay between training characteristics, training design, learning spaces and work environment factors in facilitating or impeding effective knowledge and skills transfer in the clinical environment. Based on the study's findings, the researcher views the potential solutions suggested by the participants as recommendations to possibly enhance the knowledge and skills transfer process. These recommendations include the need for training on mentoring, the use of seminars to improve personal skills, active engagement between qualified radiographers and students, initiatives to bridge the gap between students and qualified radiographers, structured student-radiographer clinical environment introduction sessions, increasing the number of clinical training sites and addressing the limited number of student placements in hospitals. The study used an infographic to explain to qualified radiographers and students these factors that influence knowledge and skills transfer between them. Future research should explore multicentre studies across universities, investigating knowledge and skills transfer in private practice settings, the development of a model that facilitates effective knowledge and skills transfer, and preceptor training on knowledge and skills transfer strategies for qualified radiographers in the clinical environment. A key limitation of this study was the data collection occurring at a single university and three public sector hospitals, which limited the diversity of insights and excluded perspectives from lecturers, radiologists and private practice settings. Additionally, the researcher's involvement in conducting and analysing the interviews, as well as the study's focus on one week of data collection, might have introduced biases and restricted in-depth participant engagement. In conclusion, the study provides diagnostic radiographers and students with a platform to voice their experiences, offering valuable insights into the enablers, barriers and possible solutions to overcome barriers to knowledge and skills transfer, which can possibly improve clinical training.
Master of Radiography (MRad) (Diagnostic)
Keywords: barriers; challenges; clinical training; community service radiographers; diagnostic radiography; enablers; infographic; knowledge and skills transfer; public healthcare sector; qualified radiographers; solutions; student radiographers; work environment; work-integrated learning; workplace learning